2023
DOI: 10.1038/s41598-023-40383-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of initial gas concentration on methane–air mixtures explosion characteristics and implications for safety management

Quansheng Jia,
Rongjun Si,
Lei Wang
et al.

Abstract: Gas explosions, particularly those involving methane–air mixtures, present considerable hazards in confined spaces, such as coal mines. Comprehending the explosion characteristics and their correlations with initial gas concentrations is vital for devising effective safety measures. This study examines the influence of initial gas concentration on explosion temperature, overpressure, and flame evolution in methane–air premixed gas explosions, utilizing a custom-built 20-L spherical explosion experimental appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the study on the propagation law of gas explosion, factors such as gas volume dose, pipeline cross-sectional area, and obstacle distribution greatly influence on the overpressure evolution laws and flame propagation characteristics of shock wave (Huang et al, 2020;Niu et al, 2021;Yan et al, 2022;Jia et al, 2023;Niu et al, 2020) established a set of experimental system in pipeline network to test the propagation characteristics of shock waves in complex areas and found that there is a pressure increasing area in the corner branch of the shock wave, but it is not affected by the flame. Zhu et al (2021) investigated the overpressure evolution law and the flame propagation process when a gas explosion occurs in U-shaped longwall coalface and H-shaped crosscut by numerical simulation, and found that a very high reflected pressure exists close to the corner but decays very fast in the free spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In the study on the propagation law of gas explosion, factors such as gas volume dose, pipeline cross-sectional area, and obstacle distribution greatly influence on the overpressure evolution laws and flame propagation characteristics of shock wave (Huang et al, 2020;Niu et al, 2021;Yan et al, 2022;Jia et al, 2023;Niu et al, 2020) established a set of experimental system in pipeline network to test the propagation characteristics of shock waves in complex areas and found that there is a pressure increasing area in the corner branch of the shock wave, but it is not affected by the flame. Zhu et al (2021) investigated the overpressure evolution law and the flame propagation process when a gas explosion occurs in U-shaped longwall coalface and H-shaped crosscut by numerical simulation, and found that a very high reflected pressure exists close to the corner but decays very fast in the free spaces.…”
Section: Introductionmentioning
confidence: 99%
“…When the gas concentration (or the concentration of coal dust suspended in the air) and oxygen concentration reach a certain limit and a high-temperature heat source is encountered, gas or coal dust explosion occurs, which not only destroys the underground ventilation network and endangers the safety of life and property but also causes a secondary explosion and brings devastating disasters to the mine. (Wang D M et al, 2021;Jia et al, 2023;Li et al, 2023). Gas and coal dust explosion includes complex physical and chemical reaction processes, and the propagation process of shock wave is a complex dynamic process of gas-solid two-phase flow coupling development.…”
Section: Introductionmentioning
confidence: 99%
“…In the study on the propagation law of gas and coal dust explosion, factors such as gas volume dose, coal dust concentration, pipeline cross-sectional area, and obstacle distribution greatly influence on the overpressure evolution laws and flame propagation characteristics of shock wave (Wang et al, 2018;Niu et al, 2019;Niu et al, 2021;Jia et al, 2023). Ma et al (2020) studied the influence of coal dust on methane-air explosion characteristics at low temperature.…”
Section: Introductionmentioning
confidence: 99%